Peranan Tata Usaha Dalam Meningkatkan Kinerja Pegawai Negeri Sipil Dinas Trasnmigrasi Kabupaten Buton - Suriani, Suriani; Tawai, Adrian; Yusuf, Muhammad (REZ PUBLICA, 2020)
This study aims to dertermine to identify describe the role of administrastion in improving the perfoermance of civil servants at the Buton regency Transmigrations Office. The method used in this study is a qualitative descriptive research method, white data collection technique was carried out by means of library research and field research using interview and documentation methods. The results of this study indicate that the role of administration in improving the performance of the Civil Servants of the Buton Regency Transmigration Service has improved considerably because the duties, functions and roles of administration in the Buton Regency transmigration service have been running optimally in accordance with the programs and main tasks and functions that have been determined and the Improvement of Civil Servant Performance The Civil Service of Transmigration in Buton Regency has not improved enough because of limited human resources and employees who do not have the will to change to improve their performance and they do not fully know their function.